Suomen ilmavoimien historia. 17, LeR 2 : lentolaivue 24, lentolaivue 26, lentolaivue 28, lentolaivue 16 - Keskinen, Kalevi; Stenman, Kari ([Kustannusliike Kari Stenman], 2001)
Summary.
Keywords: Lentorykmentti 2; hävittäjät; joukko-osastot; ilmavoimat; talvisota; jatkosota; ilmasota; sotilaslentokoneet; sotilasilmailu; lentäjät; historia